Bacterial Contamination of Sanandaj Azad Dam Lake in Kurdestan Province in 2015-16 - zahra yaghoubzadeh; Resa safari (Mashhad University of Medical Sciences, 2018)
Background and objective: Biological assessment of water resources is of particular importance and the presence of pathogens in these resources affects the health of consumers. The aim of this study was to determine the bacterial contamination of water including total coliforms, fecal coliforms and fecal streptococci in the Azad dam lake.   Methods and Materials: In this study, Sanandaj Azad dam water was evaluated for the indicator bacteria during one year (from May 2015 to June 2016). Sampling was performed from five stations in the areas of lake, transients and river. Statistical analysis of the obtained data was accomplished by ANOVA and Duncan tests using SPSS 18 software (P